PROSPEK PARIWISATA HALAL DI IBU KOTA NUSANTARA: PERSPEKTIF MAQASID SYARIAH - Aulia Rachman,; Maisyarah Rahmi Hasan, (Journal of Innovation Research and Knowledge, 2024)
This study explores the prospects for developing halal tourism in the Nusantara Capital City (IKN) through the lens of Maqasid Syariah. IKN, as a major project involving the relocation of Indonesia's capital, presents unique opportunities and challenges for the tourism sector, including halal tourism, which emphasizes Islamic values. The background of this research stems from the need to understand how the principles of Maqasid Syariah can be applied in the development of tourism that not only meets halal standards but also supports the holistic well-being of the community. The methodology employed in this study is a qualitative approach, involving document analysis and in-depth interviews. Data was gathered from various sources, including religious decrees (fatwas) from scholars, government policies related to IKN, and relevant literature on Maqasid Syariah and halal tourism. The research findings indicate that the application of Maqasid Syariah in halal tourism within IKN holds significant potential to create a tourism environment that not only adheres to halal standards but also contributes to sustainable development, social inclusivity, and the improvement of the community's quality of life. However, the primary challenge lies in the need for synergy among stakeholders to maintain a balance between economic, environmental, and spiritual needs in the context of developing this new capital city